Sensitivity-Enhanced U-Shaped Fiber SERS Probe With Photoreduced Silver Nanoparticles - Zhen Yin; Youfu Geng; Xuejin Li; Xiaoling Tan; Xueming Hong (IEEE Photonics Journal)
This paper presents a novel U-shaped fiber surface-enhanced Raman scattering (SERS) spectra probe with high-performance remote sensing based on femtosecond laser ablation and deposition of photoreduced silver nanoparticles. As the width of the U-shaped structure is around 12 $μ\text{m}$ , the sensitivity is enhanced about four times more than that of a single-endface-based fiber SERS probe. The experiment results show that there is a nonlinear relationship between the SERS signal and the width of the U-shaped structure, whereas the SERS signal is sharply decreased with the increasing width of the U-shape. Our U-shaped fiber SERS probe shows a feasible method for high-performance, real-time, and remote measurement of the SERS signal in biochemical analysis.